Performance Motivation of Taekwondo Athletes: Coach-Athlete Relationship - Nugroho Arief Setiawan; Rizky Kinanti; Fitri Agung Nanda (Journal of Coaching and Sports Science, 2023)
Without motivation, an athlete will not feel motivated to perform optimally and will be desperate if he fails. The research was conducted to present a motivational relationship between coaches and athletes that describes how coaches can influence athlete motivation. The study was conducted on 62 taekwondo athletes. The instruments to collect data were a motivation scale with 27 items (? = 0.912) and the (CART-Q) Coach-Athlete Relationship Questionnaire with 22 items (? = 0,948). The data analyzed was assisted by the SPSS for Windows version 25. The results obtained from the calculation of the product-moment correlation were the r-value was 0.471, and the r2 value was 0.222, with p lower than 0.001. Thus, there was a relationship between coach-athlete relationship and performance motivation. The psychological processes in which constructive behavior positively influences intrinsic and extrinsic motivations were self-determined by athletes.